COMMUNITY STRUCTURE OF FISH SPECIES IN THE BATANG BUNGO RIVER, BUNGO DISTRICT, JAMBI PROVINCE - Hertati, Rini; Eriza, Mas (Asian Journal of Aquatic Sciences, 2023)
This research looks at the types and diversity of fish, dominance index, evenness index, and richness index of fish species found in the Batang Bungo River, Jambi Province, Indonesia. This research was conducted from March to May 2022 at III stations. Station I Dusun Buat, station II Dusun Rantau Pandan, and station III Dusun Rantau Duku. The fishing equipment used are gillnets, nets, traps, shooting, longline fishing, and fixed fishing using local fishermen. The types of fish caught were 18 species in 5 orders, 14 genera from the Cypriniformes order, one genus from the Labyrinthici order, one genus from the Perciformes order, one genus from the Siluriformes order, and one genus from the tetraodontiformes order, the total number caught was 505 fish. The fish species diversity index (Hˈ) is in the medium category with a value of 2,576, the species evenness index (E) 0.891, the dominance index (C') 0.095, and the species richness (R) 2.731.